The role of multinationals in the world economy - Jan Winiecki (Intereconomics, 1980)
Based on trends observed during the 'sixties, a number of forecasts have projected an increasing domination by multinational corporations of the Western economies. By confronting them with the available empirical evidence of the 'seventies, Dr. Winiecki reveals some striking discrepancies between these forecasts and the realities of the past decade, the interpretation of which may contribute to a more realistic assessment of the future role of multinational corporations.
Keywords: 330; Private Investment